Participation in life situations by persons with systemic sclerosis. (May 2015) - Poole, Janet L.; Chandrasekaran, Annandhi; Hildebrand, Kristal; Skipper, Betty
Abstract Purpose: To measure the frequency of participation in life situations. Methods: A sample of 83 persons with systemic sclerosis (SSc) completed questionnaires regarding the presence and severity of disease symptoms, disability [the Health Assessment Questionnaire (HAQ)], depression [the Center for Epidemiologic Studies Depression Scale (CES-D)], and participation [the Adelaide Activities Profile (AAP)]. On the AAP, individuals rate the frequency of participation in four domains: domestic chores, household maintenance, service to others and social activities. Results: Participants were predominantly female, married, educated, white, and had diffuse SSc. Mean age was 53.7 years and mean disease duration was 9.9 years. On the AAP, participation was significantly more frequent for domestic chores than for household maintenance, service to others, and social activities. More fatigue (p < 0.05), disability (p < 0.001), and fatigue (p < 0.05) resulted in lower total AAP scores. More fatigue, pain, severe gastrointestinal symptoms, and depression related to lower household maintenance scores, while the presence of ulcers and more disability and depression were associated with lower domestic chores scores. Conclusions: Participation in life situations in persons with SSc is related to higher disability, depression, and severity of disease symptoms. Interventions to address the disability, depression and symptoms may increase participation. Implications for Rehabilitation People with systemic sclerosis (SSc) have restrictions in participation including domestic chores, household maintenance, service to others compared to a normative sample. For practitioners, these findings show the need to assess participation in addition to impairments and activity limitations in persons with SSc. The Adelaide Activities Profile could be used to measure participation. Our findings also suggest that interventions addressing fatigue, disability and depression, may improve participation.